A transcriptional switch underlies commitment to sexual development in malaria parasites. - Kafsack, B; Rovira-Graells, N; Clark, T; Bancells, C; Crowley, V; Campino, S; Williams, A; Drought, L; Kwiatkowski, D; Baker, D; Cortés, A; Llinás, M (2014)
The life cycles of many parasites involve transitions between disparate host species, requiring these parasites to go through multiple developmental stages adapted to each of these specialized niches. Transmission of malaria parasites (Plasmodium spp.) from humans to the mosquito vector requires differentiation from asexual stages replicating within red blood cells into non-dividing male and female gametocytes. Although gametocytes were first described in 1880, our understanding of the molecular mechanisms involved in commitment to gametocyte formation is extremely limited, and disrupting this critical developmental transition remains a long-standing goal. Here we show that expression levels of the DNA-binding protein PfAP2-G correlate strongly with levels of gametocyte formation. Using independent forward and reverse genetics approaches, we demonstrate that PfAP2-G function is essential for parasite sexual differentiation. By combining genome-wide PfAP2-G cognate motif occurrence with global transcriptional changes resulting from PfAP2-G ablation, we identify early gametocyte genes as probable targets of PfAP2-G and show that their regulation by PfAP2-G is critical for their wild-type level expression. In the asexual blood-stage parasites pfap2-g appears to be among a set of epigenetically silenced loci prone to spontaneous activation. Stochastic activation presents a simple mechanism for a low baseline of gametocyte production. Overall, these findings identify PfAP2-G as a master regulator of sexual-stage development in malaria parasites and mark the first discovery of a transcriptional switch controlling a differentiation decision in protozoan parasites.